SISTEM AKUNTANSI PEMBELIAN PERSEDIAAN SUKU CADANG TRUCK HYNO PADA CV MITRA BERSAMA ABADI DI TANJUNG REDEB KABUPATEN BERAU (ACCOUNTING STUDY PROGRAM, UNIVERSITAS MUHAMMADIYAH BERAU, 2019)
The purpose of this study was to find out the Accounting System for Purchasing Spare Parts Inventory at CV Mitra Bersama Abadi in Tanjung Redeb, Berau Regency, was in accordance with the theory of Accounting Systems. While the usefulness that is expected by the author of the results of this study is that it can be used to apply the theory obtained into the real situation contained in the field and as an information material for CV Mitra Bersama Abadi in Tanjung Redeb, Berau Regency. In addition, it is expected that the results of this study can be the next comparison that wants to carry out research on the problem of purchasing accounting systems. Based on the results of the analysis it can be concluded that the accounting system and internal control of purchasing truck hyno spare parts inventory at CV Mitra Bersama Abadi have not been in accordance with the elements of the purchasing accounting system and internal control components. There are still many principles of the purchasing accounting system that have not been able to be applied to CV Mitra Bersama Abadi. This is reflected in the existence of an unclear organizational structure, the existence of a double job between the purchasing function and the acceptance function, the lack of documents used and the absence of document archiving in every function that exists.